2009
DOI: 10.9775/kvfd.2010.1932
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Varying of Vegetation Harvested Hungarian Vetch and Wheat Mixture on Nutrient Content, Degradation Kinetics, in vitro Digestibility and Relative Feed Value

Abstract: Hungarian vetch intercropped with wheat (50%:50%) planted at dryland in Autumn, and were harvested 7 times at 1 wk intervals throughout mid June and late July. The aim of study was to determined the effects of varying harvested of the mixture on nutrient content,in vitro digestibility, relative feed value (RFV) and rumen degradation kinetics. While harvest effect did not differ hay of Hungarian vetch + wheat on dry matter (DM), ash and organic matter, NDF and ADF ratios increased, and the crude protein ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In the mixtures, decreased CPYs were observed with decreasing HV ratios. While most researchers found the highest CPRs and yields with 60% or higher HV in the mixture (Albayrak et al 2004;Karadag and Buyukburc 2004;Balabanli and Turk 2006;Lithourgidis et al 2006;Bingol et al 2007;Yolcu et al 2009;Budak et al 2011), some others observed the highest yields in equal mixtures (50%-50%) (Basbag et al 1999;Gunduz 2010;Aksoy and Nursoy 2010) and 60% cereal mixtures (Bedir 2010). HV contains remarkably more CP than grasses and its mixtures with grasses contain more CP than the sole sowing of AR.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the mixtures, decreased CPYs were observed with decreasing HV ratios. While most researchers found the highest CPRs and yields with 60% or higher HV in the mixture (Albayrak et al 2004;Karadag and Buyukburc 2004;Balabanli and Turk 2006;Lithourgidis et al 2006;Bingol et al 2007;Yolcu et al 2009;Budak et al 2011), some others observed the highest yields in equal mixtures (50%-50%) (Basbag et al 1999;Gunduz 2010;Aksoy and Nursoy 2010) and 60% cereal mixtures (Bedir 2010). HV contains remarkably more CP than grasses and its mixtures with grasses contain more CP than the sole sowing of AR.…”
Section: Resultsmentioning
confidence: 98%
“…While several researchers reported the highest green herbage and hay yields of HV mixtures as 66%-87.5% (Albayrak et al 2004;Yolcu et al 2009;Budak et al 2011;Koc et al 2013), others reported the highest values for equivalent rate mixtures (50%-50%) (Karadag and Buyukburc 2004;Gunduz 2010;Aksoy and Nursoy 2010;Nadeem et al 2010). Contrary to other researches, Balabanli and Turk (2006), Tuna and Orak (2007), and Bedir (2010) reported the highest yield values for cereals mixture rates of 75%-80%.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The IVTD DM values showed no significant differences (P >0.05) among the control and treatment groups. The in vitro dry matter digestibility levels of common vetch/wheat hay harvested at different times were in the range of 57.37 to 70.48% (Aksoy & Nursoy, 2010). The reported IVTD DM values for common vetch were 58.06 % and 74.95% in 2003and 2004, respectively (Yucel & Ayasan, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…With mixed cultivation, harvesting becomes easier ( Kusvuran et al, 2014). It has been reported by the researchers that the most suitable form of time in the plantings mixed with the wheat crops is 30-36% of the dry matter of the plant mixtures or in the milk stage of wheat (Aksoy and Nursoy, 2010). On the other hand, triticale plant is a hybrid of wheat and rye and has been obtained as a result of long-term improvement studies in many countries.…”
Section: Introductionmentioning
confidence: 99%